Rancangan Sistem Informasi Timesheet Alat Berat Berbasis User Centered Design - Michael Elyas Ernawan; Eko Sediyono (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Along with developments in the field of technology, companies are increasingly being triggered to use advanced technology as a tool or medium to survive and win the increasingly fierce competition. PT. Sarana Bangun Pusaka is engaged in the construction sector. In the construction sector, heavy equipment is a tool used to simplify the construction work process, so that development becomes faster, easier, and the results are in line with expectations. PT. Sarana Bangun Pusaka has difficulty recording field work hours and recording what workers are doing. Reports used are also still recorded manually. Seeing this need PT. Sarana Bangun Pusaka has also developed a report system that shows project activities currently underway in the field. This system aims to obtain accurate and efficient data. The development of this system uses the User Centered Design (UCD) method which is structured from specify the context of use, specify user and organizational requirements, produce design solutions, evaluate designs against user requirements. The development of this information system is designed to build a timesheet information system that has advantages in processing field heavy equipment report data and data on the work being done. The use of the web in this system aims to be accessible using a cellphone, quickly, and efficiently. This system has been tested by blackbox testing with results that can make it easier to manage data and can provide information about PT. Sarana Bangun Pusaka.